The complexity of cooperation : agent-based models of competition and collaboration - Axelrod, Robert M. (Princeton University Press, 1997)
Robert Axelrod is widely known for his groundbreaking work in game theory and complexity theory. He is a leader in applying computer modeling to social science problems. His book The Evolution of Cooperation has been hailed as a seminal contribution and has been translated into eight languages since its initial publication. The Complexity of Cooperation is a sequel to that landmark book. It collects seven essays, originally published in a broad range of journals, and adds an extensive new introduction to the collection, along with new prefaces to each essay and a useful new appendix of additio.
Keywords: Cooperativeness.; Competition.; Conflict management.; Adaptability (Psychology); Adjustment (Psychology); Computational complexity.; Social systems -- Computer simulation.; Coopération (Psychologie); Gestion des conflits.; Adaptation (Psychologie); Ajustement (Psychologie); Complexité de calcul (Informatique); Systèmes sociaux -- Simulation par ordinateur.; SELF-HELP -- Personal Growth -- Success.; Competition; Computational complexity; Conflict management; Cooperativeness; Social systems -- Computer simulation; Ajustamento.